2009
DOI: 10.1152/ajplung.90622.2008
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal organic dust exposure-induced airway adaptation response marked by persistent lung inflammation and pathology in mice

Abstract: Animal models to study these mechanisms are limited. This study investigated the effects of single vs. repetitive dust-induced airway inflammation in mice by intranasal exposure method. Mice were exposed to swine facility dust extract (DE) or saline once and once daily for 1 and 2 wk. Dust exposure resulted in increased bronchoalveolar lavage fluid neutrophils and macrophages after single and repetitive exposures. Lavage fluid TNF␣, IL-6, keratinocyte chemoattractant, and macrophage inflammatory protein-2 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
258
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(284 citation statements)
references
References 47 publications
25
258
1
Order By: Relevance
“…Inhalation of endotoxins and carbon dioxide at levels above the recommended health threshold limits (Mc Donnell et al, 2008) can lead to acute and chronic airway inflammation (Schierl et al, 2007). Poole et al (2009) reported increased cellular inflammation, predominated by neutrophils, in mouse BALF following a single intranasal instillation of DE.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Inhalation of endotoxins and carbon dioxide at levels above the recommended health threshold limits (Mc Donnell et al, 2008) can lead to acute and chronic airway inflammation (Schierl et al, 2007). Poole et al (2009) reported increased cellular inflammation, predominated by neutrophils, in mouse BALF following a single intranasal instillation of DE.…”
Section: Discussionmentioning
confidence: 97%
“…In humans and animals, lung challenge with Lipopolysaccharide (LPS) causes a neutrophil-rich inflammatory responses and intranasal instillation of swine confinement dust extracts in mice has been shown to lead to increased cellular inflammation that is predominated by neutrophils (Sandström et al, 1994) (Jagielo et al, 1996;Poole et al, 2009). Differential cell analysis of the cells collected from the BAL show that neutrophils were the predominant cell type detected in the in the lungs 24 h after LPS and 10% DE challenge (Fig.…”
Section: Analysis Of Inflammation; Cellular Influx and Protein Expresmentioning
confidence: 98%
“…Airway inflammation can lead to loss of lung function, as measured by the decrease in forced expiratory air in one second or less (Costa et al, 2007). Poole et al (2009b) reported increased cellular inflammation, predominated by neutrophils and neutrophils and macrophages, in mouse BALF following a single and 1/2 week intranasal instillation of DE, respectively. Mice continuously exposed to swine CAFO dust via nebulizer for 4 h developed BALFneutrophilia (Mueller-Anneling et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The dust extract was prepared using a protocol similar to Poole et al (2009b). Briefly, several grams of settled dust from raised surfaces were collected from the gestation and farrowing rooms at North Carolina A and T State University's Swine Research Unit and brushed into a zip top bag.…”
Section: Dust Collection and Extract Preparation For In Vivo And In Vmentioning
confidence: 99%
“…A major purpose of the investigation was to compare and contrast the effects of diacetyl and 2,3-pentanedione in airways in vivo and in vitro. In the first series of experiments, alterations were determined in respiratory mechanics, that is, lung resistance and dynamic compliance (R L and C dyn , respectively), as well as reactivity to inhaled MCh, following diacetyl or 2,3-pentanedione inhalation (Poole et al, 2009;Yao et al, 2010). It was of interest to identify the concentration range over which diacetyl and 2,3-pentanedione may produce such effects.…”
mentioning
confidence: 99%